2021
DOI: 10.3390/biology10121276
|View full text |Cite
|
Sign up to set email alerts
|

A Conservative Replacement in the Transmembrane Domain of SARS-CoV-2 ORF7a as a Putative Risk Factor in COVID-19

Abstract: The ongoing COVID-19 pandemic follows an unpredictable evolution, driven by both host-related factors such as mobility, vaccination status, and comorbidities and by pathogen-related ones. The pathogenicity of its causative agent, SARS-CoV-2 virus, relates to the functions of the proteins synthesized intracellularly, as guided by viral RNA. These functions are constantly altered through mutations resulting in increased virulence, infectivity, and antibody-evasion abilities. Well-characterized mutations in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 40 publications
3
12
0
Order By: Relevance
“…The association of ORF7a: P45L mutation with disease severity in Uzbekistan, reported for the first time herein ( Table 10 ), is in concordance with previous research, that the stabilizing mutation in the ORF7a of a SARS-CoV-2 was associated with the increased severity and lethality in a group of Romanian patients, despite a lower viral copy number and a lower number of associated comorbidities [ 38 ].…”
Section: Discussionsupporting
confidence: 91%
“…The association of ORF7a: P45L mutation with disease severity in Uzbekistan, reported for the first time herein ( Table 10 ), is in concordance with previous research, that the stabilizing mutation in the ORF7a of a SARS-CoV-2 was associated with the increased severity and lethality in a group of Romanian patients, despite a lower viral copy number and a lower number of associated comorbidities [ 38 ].…”
Section: Discussionsupporting
confidence: 91%
“…In addition, it died out in the immunocompetent population 1.5 months after it was detected (39). Another study identified a mutation in the transmembrane domain of ORF7a that improved its stability and caused severe infection despite low viral loads (40) although the mechanism behind this has not been determined. A mouse model of COVID19 using DORF7a rSARS-CoV-2 showed that this virus had a replication defect in vitro, was cleared more efficiently from the nasal turbines than intact virus, and lung lesions caused by it were also resolved sooner (28).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the 44 patients described here, the AASs S81P occurred twice in P14 and P22 (4.5%), and the A105V, which occurred in P9, has been characterized before. In a 62-patient Romanian cohort, Lobiuc et al (2021) showed that 27.5% were infected with the A105V AAS, and they experienced a twofold higher death rate than others without A105V. The researchers then did a bioinformatic analysis of this change and predicted an increased stability by allosteric effects (Lobiuc et al, 2021).…”
Section: Orf7amentioning
confidence: 99%
“…In a 62-patient Romanian cohort, Lobiuc et al (2021) showed that 27.5% were infected with the A105V AAS, and they experienced a twofold higher death rate than others without A105V. The researchers then did a bioinformatic analysis of this change and predicted an increased stability by allosteric effects (Lobiuc et al, 2021).…”
Section: Orf7amentioning
confidence: 99%